Embodied Aesthetics and Philosophy in the Traditions of Sal-seri, Stilt Walkers, and Tricksters in Kazakh Steppe Performance - Bokebayev, N.A.; Masaeli, M.; Omirbekova, A.O. (Karagandy University of the name of acad. E.A. Buketov, 2025)
This article explores the philosophical dimensions of Kazakh performative traditions, focusing on the aesthetic, spiritual, and social significance of sal-seri culture, stilt walkers (agashayak), and tricksters within the nomadic heritage of the Kazakh Steppe. Drawing from historical, ethnographic, and folkloric sources, the paper argues that these artistic forms are not mere entertainments but constitute complex embodied philosophies of being, resistance, and communal memory. Through the lens of cultural aesthetics and performative identity, we examine how sal-seri figures — poet-singers, warriors, craftsmen, and spiritual intermediaries — acted as agents of ethical critique, poetic expression, and social cohesion. The syncretic blend of music, humor, ritual, and physical virtuosity embedded in these practices offers insight into an indigenous Kazakh philosophy of art rooted in mobility, improvisation, and ecological attunement. These traditions also prefigure contemporary notions of performativity, particularly in their fusion of artistic, ethical, and existential domains.
Keywords: agashayak; nomadic ethics; tricksters; cultural memory; sal-seri; Kazakh philosophy of art